1997
DOI: 10.1111/j.1439-0396.1997.tb00745.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salinomycin on in vitro caecal fermentation in pigs

Abstract: Summary The effect of salinomycin was investigated in anaerobic incubations of the pig caecal contents collected at slaughter, diluted with buffer and either supplied with starch or not. Salinomycin was present in cultures at 0, 2, 5 and 10 mg/l. In the whole range of concentrations that were tested, salinomycin significantly increased the production of propionate at the expense of acetate and butyrate. At 5 and 10 mg/l, these fermentation shifts were accompanied by a significant decrease of the total VFA, gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
5
1
Order By: Relevance
“…Data presented in Table 1 do not differ much from our previous findings in pigs fasted for 16 h before slaughter (Marounek et al 1997). Crude protein (calculated using the factor 6.25) and true protein (determined by the Lowry method) represented 16.1 and 12.4% of digesta DM, respectively (Table 2).…”
Section: Resultsmentioning
confidence: 44%
“…Data presented in Table 1 do not differ much from our previous findings in pigs fasted for 16 h before slaughter (Marounek et al 1997). Crude protein (calculated using the factor 6.25) and true protein (determined by the Lowry method) represented 16.1 and 12.4% of digesta DM, respectively (Table 2).…”
Section: Resultsmentioning
confidence: 44%
“…In our study, the methanogenesis in WBPHs increased after the addition of wheat bran. Methane production after 8 h of the in vitro incubation of pig caecal contents with starch amounted to 6.14 mmol/l (Marounek et al 1997). The rate of methanogenesis in WBPH caecal inocula appeared higher in our experiment, but this may be caused by longer incubation time.…”
Section: Doi: 1017221/7/2016-cjascontrasting
confidence: 51%
“…Impact of diet composition and narasin supplementation on pig performance and on energy, nutrient, and fiber digestibility in 9-to 23-kg pigs, Exp. ardson et al, 1976;Schelling, 1984;Holzgraefe et al, 1985a;Russell, 1987;Marounek et al, 1997;Wuethrich et al, 1998), we expected an effect on nutrient digestibility and animal performance due to narasin supplementation. In Exp.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, Thacker et al (1992) and Van Lunen et al (1992) reported no effect of ionophore supplementation on growing pig performance. Ionophores may also impact hind gut bacterial fermentation processes as shown by a decrease in the acetate:proprionate ratio in pigs fed lasalocid (Holzgraefe et al, 1985a) or salinomycin (Marounek et al, 1997). Holzgraefe et al (1985b) reported that lasalocid added to sows diets containing either CSBM or corn-hay-based diet numerically improved fiber and N digestion, but not GE utilization, while Moore et al (1986a) reported that salinomycin influenced GE and N utilization in pigs fed diets containing wheat bran, but not in pigs fed a CSBM or a diet containing oat hulls.…”
Section: Introductionmentioning
confidence: 99%